2021
DOI: 10.1371/journal.pntd.0009794
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neuropathic pain in leprosy patients with relapse or treatment failure by infrared thermography: A cross-sectional study

Abstract: Background Neuropathic pain (NP) is one of the main complications of leprosy, and its management is challenging. Infrared thermography (IRT) has been shown to be effective in the evaluation of peripheral autonomic function resulting from microcirculation flow changes in painful syndromes. This study used IRT to map the skin temperature on the hands and feet of leprosy patients with NP. Methodology/Principal findings This cross-sectional study included 20 controls and 55 leprosy patients, distributed into 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Marins's study reported considerable thermal equilibrium for the contralateral ROI and nonsignificant differences in the hands, ventral leg, abdomen, and lower back in terms of sex 17 . In Tiago's research, 41 areas were selected from the hands and feet of patients with leprosy and controls, except for two palmar points and one dorsal point; all patients exhibited significant temperature asymmetry at almost all points evaluated on their hands 35 . The left and right hands are symmetrical according to the body distribution, and the temperature recorded herein is from the fingertips of both hands; therefore, the symmetry evaluation was included in the data analysis process.…”
Section: Discussionmentioning
confidence: 99%
“…Marins's study reported considerable thermal equilibrium for the contralateral ROI and nonsignificant differences in the hands, ventral leg, abdomen, and lower back in terms of sex 17 . In Tiago's research, 41 areas were selected from the hands and feet of patients with leprosy and controls, except for two palmar points and one dorsal point; all patients exhibited significant temperature asymmetry at almost all points evaluated on their hands 35 . The left and right hands are symmetrical according to the body distribution, and the temperature recorded herein is from the fingertips of both hands; therefore, the symmetry evaluation was included in the data analysis process.…”
Section: Discussionmentioning
confidence: 99%